Optical Absorption Enhancement in Amorphous Silicon Films and Solar Cell Precursors Using the Aluminum-Induced Glass Texturing Method - Nasim Sahraei; Selvaraj Venkataraj; Premachandran Vayalakkara; Armin G. Aberle (International Journal of Photoenergy)
One of the key issues of thin-film silicon solar cells is their limited optical absorptance due to the thin absorber layer and the low absorption coefficient for near-infrared wavelengths. Texturing of one or more interfaces in the layered structure of these cells is an important technique to scatter light and enhance the optical pathlength. This in turn enhances the optical absorption of the solar radiation in the absorber layer and improves the solar cell efficiency. In this paper we investigate the effects of textured glass superstrate surfaces on the optical absorptance of intrinsic a-Si:H films and a-Si:H p-i-n thin-film solar cell precursors deposited onto them. The silicon-facing surface of the glass sheets was textured with the aluminium-induced glass texturing method (AIT method). Absorption in both intrinsic silicon films and solar cell precursor structures is found to increase strongly due to the textured glass superstrate. The increased absorption due to the AIT glass opens up the possibility to reduce the absorber layer thickness of a-Si:H solar cells.